Analisis Nilai Karakter Sabar dalam Film Merindu Cahaya de Amstel untuk Pembelajaran PAI - yunus, fakhirah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
Patient character education is a very fundamental thing, there is a need for education to face life's problems patiently. Educators are required to be more varied in educating students, so there is a need for real alternative practice activities to overcome this. The film Merindu Cahaya de Amstel depicts many patient characters who can be used as a learning tool. Therefore, the aim of this research is to describe the patient character values ​​found in the film Merindu Cahaya De Asmtel and their relevance to Islamic religious education. The approach used in this research is qualitative with a content analysis method. The data collection technique in this research uses document study, the researcher as a tool for observing speech and images with elements of patient character, then clarifying them based on categories of patient character, then explaining and analyzing how relevant they are to Islamic Religious Education, to produce an in-depth interpretation regarding the value of patient character. with the object of study is the film Merindu Cahaya de Amstel. Based on the results of the research conducted, there were 40 patient scenes, 20 of which were in the form of speech and the other 20 were in the form of behavior. The character of patience expressed is divided into several things, including: 1. Patience in holding back anger, 2. Patience in forgiving, 3. Patience in worship, 4. Patience in accepting fate, 5. Patience not to hurt other people, 6. Patience with unkind treatment good from other people, 7. Be patient in disaster.